The Management of Midwifery Care on 19 Years Old GIP0A0 Gestational Age 11 Weeks 3 Days with Incomplete Abortion at Pringsewu Regional General Hospital - Juwita Desri Ayu; Linda Puspita (Universitas Aisyah Pringsewu, 2023)
Incomplete abortion is bleeding from the uterus in less than 20 weeks of pregnancy, accompanied by some of the products of conception that have come out of the uterine cavity, and some are still left behind. Methods The research design is descriptive quantitative observational with the type of Case Report (CARE). This study aims to carry out the Management of Midwifery Care on 19 Years Old GIP0A0 Gestational Age 11 Weeks 3 Days with Incomplete Abortion at Pringsewu Regional General Hospital in 2017 by applying Varney's 7 steps and midwifery’s documentation done in the form of SOAP (Subjective, Objective, Assessment and Plan). Results in A case study was conducted with a diagnosis of incomplete abortion based on comprehensive anamnesis and physical examination data. Mrs.”H” came to the Pringsewu Regional General Hospital with the main complaint of bleeding in the form of spots from the birth canal since February 15th, 2022. Then, on February 16th, 2017, there was bleeding in the formation of clots from the birth canal. The patient looks weak, conscious composmentis, blood pressure 130/80 mmHg, pulse 80 beats/minute, respiratory 20 breaths/minute, body temperature 36.5ºC, fundal height two fingers above the symphysis pubis, Ostium Uteri Externum/ Ostium Uteri Internum is closed. Ultrasound examination with residual tissue impressions, anteflexed uterus, and Femur Length (-), it is possible that an incomplete abortion will occur. On Mrs.